Rhodium Catalyzed Arylative Cyclization of Diynes With Arylboronic Acids - Ürer, Bağdagül; Artok, Levent (Izmir Institute of Technology, 2009)
This study reveals that exo-conjugated cyclic dienes can be synthesized by rhodium(I) catalyzed arylative cyclization of unsymmetric diyne molecules with arylboronic acids. Cyclic dienes are important reagents in organic chemistry because they easily undergo [4+2] cycloaddition reactions with dienophiles and also, they are useful intermediates in the synthesis of complex polycyclic compounds. To form carbon.carbon bonds, transition metal catalyzed arylative cyclization reactions of unsaturated reagents with arylboronic acids is a useful and efficient way in organic synthesis. For this purpose, rhodium catalyzed arylative cyclization of enyne type unsaturated reagents have been found significantly in literature. In this study, unsymmetric diyne type molecules were reacted with arylboronic acids in the presence of a rhodium complex under argon atmosphere. The reactions proceeded effectively in methanol as a solvent under very mild reaction conditions.
Thesis (Master)--İzmir Institute of Technology, Chemistry, İzmir, 2009
Includes bibliographical references (leaves: 54-57)
Text in English; Abstract: Turkish and English
xii, 118 leaves
Keywords: QD412.B1 .U75 2009; Organoboron compounds; Rhodium catalysts; Diolefins